2017
DOI: 10.2527/tas2017.0054
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome virus reduces feed efficiency, digestibility, and lean tissue accretion in grow-finish pigs1

Abstract: Porcine reproductive and respiratory syndrome (PRRS) virus is a major swine virus that causes reproductive impairment in sows, as well as respiratory disease, reduction in growth rates, and mortalities in all ages of pigs. The objective of this study was to quantify the impact PRRS has on grower-finisher pig feed efficiency and tissue accretion rates. Thirty PRRS naïve, littermate pairs of maternal line Choice Genetics gilts (33.6 ± 0.58 kg BW) were selected and pairs split across 2 barns consisting of 5 pens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
(39 reference statements)
4
18
0
Order By: Relevance
“…There was no diet × PRRSV interaction ( P > 0.10) at either time point or any effect of PRRSV on any ATTD coefficients evaluated. No effect of PRRSV on ATTD coefficients is in agreement with a previous study from our group ( Schweer et al, 2016b ); however, this is in contrast with another study from our group ( Schweer et al, 2017 ). In the later study, pigs were housed in a commercial barn and not in a BSL2 facility, and could have been exposed to secondary pathogens.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…There was no diet × PRRSV interaction ( P > 0.10) at either time point or any effect of PRRSV on any ATTD coefficients evaluated. No effect of PRRSV on ATTD coefficients is in agreement with a previous study from our group ( Schweer et al, 2016b ); however, this is in contrast with another study from our group ( Schweer et al, 2017 ). In the later study, pigs were housed in a commercial barn and not in a BSL2 facility, and could have been exposed to secondary pathogens.…”
Section: Resultssupporting
confidence: 91%
“…Previous research completed by our group ( Schweer et al, 2016b , 2017 ) and others ( Greiner et al, 2000 ; Escobar et al, 2004 ) have reported reduced growth performance and feed efficiency due to PRRSV infection. Additionally, protein and fat accretion are reduced during a PRRSV challenge both acutely ( Escobar et al, 2004 ) and throughout the entire finishing period ( Schweer et al, 2017 ). Dietary strategies are of interest to recover lost growth performance and promote earlier clearance of virus in pathogen-challenged pigs.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations